Fever in pregnancy and its maternal and fetal outcome at tertiary care level - Poovathi, M.; Prasanna, N. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: The fever during pregnancy is the omnious sign. Early detection and prompt management of fever prevents maternal mortality and morbidity. Any maternal hyperthermia (>38.9°C) potentially affect the fetus. Hence study was conducted to know the outcome of fever in pregnancy. Methods: To study the outcome of pregnant women admitted with fever in obstetrics ward at MGMGH, Trichy over the period of 6 months from July 2017 to December 2017. Results: The incidence of fever was 6%. In this study the most common cause was viral fever among which dengue fever was most common. Hence outcome depends on its impact on pregnant mother and fetus. Many preterm labour (24%) were noted in this study which needs NICU admission of babies. Maternal mortality was 25%, most of it were associated with DIC, IUD and one or two combined risk factors. Conclusions: The incidence of fever was 6%. In this study the most common cause was viral fever among which dengue fever was most common. Hence outcome depends on its impact on pregnant mother and fetus. Many preterm labour (24%) were noted in this study which needs NICU admission of babies. Maternal mortality was 25%, most of it were associated with DIC, IUD and one or two combined risk factors.